Marketing native crops to improve rural Andean livelihoods - Devaux, A.; Ordinola, M.; Andrade-Piedra, J.L.; Thiele, Graham (University of Bern, 2021)
Native potatoes are important in livelihood strategies for most poor Andean families. A systems-oriented approach for fostering pro-poor development in value chains has helped to identify business opportunities, facilitate collaboration among value chain actors and enhance information flows to increase competitiveness.